Comparison of Mindfulness With and Without Practice Among Women in Custody - Song, Xiaolan (Criminal justice and behavior, 2021)
This study aimed to explore the effects of standardized mindfulness-based cognitive therapy (MBCT) and MBCT training without practice on the negative mood of women in custody. Eighty participants were assigned to the standard MBCT group, theoretical learning group, or waitlist control group. We assessed participants’ mindfulness, stress, depression, and anxiety before and after the interventions. The results showed that, compared with controls, participants in the standard MBCT course showed significant improvement in depression and state anxiety; they also showed significant improvement in perceived stress. Although similar effects on depression were observed in the theoretical learning group, this group did not show decreased anxiety. These findings suggest that practice plays a crucial role in MBCT’s effects on female prisoners’ mental health. This study provides important insights into the application of mindfulness-based interventions (MBIs) as promising treatments for improving responsivity factors of the risk–need–responsivity model for female incarcerated populations.